PROSPECTS OF RNA-INTERFERENCE IN THE TREATMENT OF HIV-INFECTION - Чернікова, Л.І.; Коваленко, Н.І. (World of Medicine and Biology, 2015)
The results of trials of RNA-interference system to inhibit HIV replication in sensitive cells at different stages of the viral life cycle and blocking CCR5 co-receptor of human cells were conducted.
Keywords: gene therapy; RNA interference; HIV infection